New cinematographers Lance Acord, Jean-Yves Escoffier, Darius Khondji, John Mathieson, Seamus McGarvey, Harris Savides - Ballinger, Alexander (London : Laurence King ; New York : Harper Design International, 2004)
diagrams, together with many stills from each film which have been carefully chosen to emphasize the specific points being discussed. Packed full of insights and original material, this book will appeal to all practising and aspiring cinematographers, as well as to anyone interested in or involved in film."--BOOK JACKET.
Includes bibliographical references and index.
All age.
Keywords: Cinematographers; Cinematographers -- Interviews